1998
DOI: 10.1002/j.1550-8528.1998.tb00324.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sibutramine on Resting Metabolic Rate and Weight Loss in Overweight Women

Abstract: SEAGLE, HELEN M., DAN H. BESSESEN, JAMES 0. HILL. Effects of sibutramine on resting metabolic rate and weight loss in overweight women. Obes Res. 1998; Sibutramine, a monoamine re-uptake inhibitor, has recently been approved by the Food and Drug Administration as a weight loss agent. Sibutramine lowers bodyweight in rodents by reducing energy intake and increasing energy expenditure. Sibutramine facilitates weight loss in human subjects, but it is not clear whether it acts on energy intake, energy expenditure,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
78
1
2

Year Published

1998
1998
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(84 citation statements)
references
References 12 publications
3
78
1
2
Order By: Relevance
“…22 This observation taken together with the present ®nding of a weak thermogenic effect of sibutramine emphasises that it may be dif®cult to detect the effect by short-term measurement of EE.…”
Section: Discussionmentioning
confidence: 48%
“…22 This observation taken together with the present ®nding of a weak thermogenic effect of sibutramine emphasises that it may be dif®cult to detect the effect by short-term measurement of EE.…”
Section: Discussionmentioning
confidence: 48%
“…This effect, however, could result in an elevation in blood pressure and a reduction in the antihypertensive benefits of weight loss. In fact, previous studies in normotensive patients reported elevations in heart rate and blood pressure associated with the use of sibutramine 15 .…”
Section: Discussionmentioning
confidence: 97%
“…Part of the effects of sibutramine is due to the inhibition of noradrenaline reuptake with the resulting maintenance of adrenergic tonus in these patients, which can be beneficial for avoiding the drop in energy expenditure that follows weight loss according to the studies by Hansen et al 14 and Seagle et al 15 . This effect, however, could result in an elevation in blood pressure and a reduction in the antihypertensive benefits of weight loss.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20,21 Increase in energy expenditure with sibutramine treatment has been reported in two studies 19,20 Journal of Human Hypertension although not in one other. 22 This possible dual mechanism of action may enhance the efficacy of sibutramine by diminishing the decrease in metabolic rate normally encountered upon initial weight loss. Because the cardiovascular side effects of sibutramine can be attributed, in part, to stimulation of the sympathetic nervous system, blocking of the cardiac ␤ 1 -adrenoceptors with ␤-blockers can be expected to reduce the magnitude of these effects.…”
Section: Discussionmentioning
confidence: 99%